Assessing peer influence on farmers' climate adaptations: An experimental adoption of index insurance and savings in Uzbekistan - Laura Moritz; Lena Kuhn; Ihtiyor Bobojonov; Thomas Glauben (Journal of Agricultural and Applied Economics, 2024)
Strengthening climate resilience requires farmers to select climate adaptation strategies like weather index insurance. Acknowledging that decision-making is not isolated, this study explores simultaneous peer imitation in climate adaptation choices consisting of index insurance, savings, and their interaction. We present results from a lab-in-the-field experiment that introduces innovative index insurance. Findings indicate significant and strong imitation attitudes. While the bigger peer surrounding seems relevant in the static perspective, the closer surrounding gains importance in the dynamic perspective. Additionally, credit, trust, and practical understanding stimulate adoption. Community-based extension interventions and credit-bundled products may increase index insurance diffusion and improve climate resilience.
Keywords: G22; O16; O12; O13; D91; 330; adoption behavior; climate adaptations; index insurance; lab-in-the-field experiment; peer imitation; savings; Uzbekistan